Women's Sexual Orientation and Occupational Tasks: Partners, Prejudice, and Motherhood - Raquel Carrasco; Ana Nuevo-Chiquero (Institute of Labor Economics (IZA), 2024)
This paper examines differences in occupational task content among women based on their sexual orientation. Using data from the American Community Survey, we find that women in same-sex couples are more likely to be employed in occupations characterized by more abstract and manual tasks, and fewer routine components. These occupations are traditionally associated with greater flexibility, accommodating career interruptions, and minimizing skill depreciation. These differences are not explained by individual or partner characteristics or by prejudice at the occupational level. Furthermore, our findings hold even after controlling for self-selection into the labor force. Heterogeneous effects by age and parental status suggest that these choices reflect long-term strategies rather than short-term responses to childbearing. This points to a complex relationship between occupational choice and fertility, influenced by the probability of labour force exit and re-entry.
Keywords: J15; J16; J71; 330; sexual orientation; occupation; intended fertility; gender wage gap